2009
DOI: 10.1083/jcb.200809044
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 1–dependent suppression of EGFR signaling promotes epidermal differentiation and morphogenesis

Abstract: Dsg1 (desmoglein 1) is a member of the cadherin family of Ca2+-dependent cell adhesion molecules that is first expressed in the epidermis as keratinocytes transit out of the basal layer and becomes concentrated in the uppermost cell layers of this stratified epithelium. In this study, we show that Dsg1 is not only required for maintaining epidermal tissue integrity in the superficial layers but also supports keratinocyte differentiation and suprabasal morphogenesis. Dsg1 lacking N-terminal ectodomain residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
257
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 197 publications
(280 citation statements)
references
References 66 publications
23
257
0
Order By: Relevance
“…A previous study reported that another isoform of Dsg, Dsg1, is expressed in suprabasal differentiated keratinocytes and is required for suppressing EGFR-extracellular signalregulated kinase (Erk) 1/2 signaling to allow for normal differentiation. 13 However, cell proliferation was not measured in this study. As we had observed that EGFR signaling promotes proliferation in Dsc2-deficient colonic epithelial cells, 7 we assessed whether EGFR signaling was altered in SK-CO15 cells lacking Dsg2.…”
Section: Egfr Signaling Is Diminished In Cells Lacking Dsg2mentioning
confidence: 90%
“…A previous study reported that another isoform of Dsg, Dsg1, is expressed in suprabasal differentiated keratinocytes and is required for suppressing EGFR-extracellular signalregulated kinase (Erk) 1/2 signaling to allow for normal differentiation. 13 However, cell proliferation was not measured in this study. As we had observed that EGFR signaling promotes proliferation in Dsc2-deficient colonic epithelial cells, 7 we assessed whether EGFR signaling was altered in SK-CO15 cells lacking Dsg2.…”
Section: Egfr Signaling Is Diminished In Cells Lacking Dsg2mentioning
confidence: 90%
“…Human cervical cancer HeLa cells and human keratinocyte line HaCaT cells were maintained in DMEM (Gibco®; Invitrogen) with 10% heat-inactivated fetal bovine serum. Human skin equivalents were generated by the Skin Disease Research Center (SDRC) at Northwestern University (NU) and used when they were fully differentiated as intact skin (42). Studies were also performed with EpiDerm skin model samples (MatTek), grown in medium provided by MatTek.…”
Section: Methodsmentioning
confidence: 99%
“…Raft cultures of HEKs were produced by the Northwestern University Skin Disease Research Center's keratinocyte core facility. Briefly, HEKs were grown to confluence in E-medium [DMEM/F12, 5% (vol/vol) FBS] with EGF (5 ng/mL) and switched to an air-medium interface for 3, 7, and 12 d (23). The raft cultures of hTCEpi cells were derived as previously described (33).…”
Section: Methodsmentioning
confidence: 99%
“…2A). To investigate this FIH-1 attenuation in HEK differentiation and increase in proliferation in a more physiologically relevant manner, we used a three-dimensional organotypic raft model of human epidermis (23). FIH-1 was detected in the nucleus and cytoplasm of cells in all but the uppermost cornified layer of raft cultures generated from FIH-1-transduced HEKs ( Fig.…”
Section: Fih-1 Expression Is Elevated In Conditions Of Abnormal Epithmentioning
confidence: 99%